2019
DOI: 10.1146/annurev-anchem-061318-115117
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Organism Analysis by Vibrational Spectroscopy

Abstract: Vibrational spectroscopy has contributed to the understanding of biological materials for many years. As the technology has advanced, the technique has been brought to bear on the analysis of whole organisms. Here, we discuss advanced and recently developed infrared and Raman spectroscopic instrumentation to whole-organism analysis. We highlight many of the recent contributions made in this relatively new area of spectroscopy, particularly addressing organisms associated with disease with emphasis on diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…As a result, we perceive vibrational spectroscopy development as a fashionable topic for health policies in the present and in the future. However, a vast array of potential applications continues to be assessed while others need further technological developments [200], for example, endoscopic disease detection in hollow organs, detection of pathogens in urine samples, detection of pathogens in blood samples, detection of pathogens in other body fluids, identifying antibiotic resistance, vibrational spectroscopy utility in pharmaceutical analysis, and recently developed infrared and Raman spectroscopic instrumentation to whole-organism analysis [204]. In this regard, further new steps are necessary involving economics and practical technology translation from the proof of concept studies.…”
Section: Future Perspectives: Framing In a Broader Vision Of Healtmentioning
confidence: 99%
“…As a result, we perceive vibrational spectroscopy development as a fashionable topic for health policies in the present and in the future. However, a vast array of potential applications continues to be assessed while others need further technological developments [200], for example, endoscopic disease detection in hollow organs, detection of pathogens in urine samples, detection of pathogens in blood samples, detection of pathogens in other body fluids, identifying antibiotic resistance, vibrational spectroscopy utility in pharmaceutical analysis, and recently developed infrared and Raman spectroscopic instrumentation to whole-organism analysis [204]. In this regard, further new steps are necessary involving economics and practical technology translation from the proof of concept studies.…”
Section: Future Perspectives: Framing In a Broader Vision Of Healtmentioning
confidence: 99%
“…Over the past decades, vibrational spectroscopy has developed into an important analytical tool with ample applications in chemistry and beyond. [22][23][24][25][26][27][28][29][30][31] Nowadays modern vibrational spectroscopy has much more to offer; detailed information on the electronic structure of a molecule and its chemical bonds is encoded in the normal vibrational modes, ready to be deciphered. With the increasing number of available high precision measured spectra complemented with theoretical calculations, vibrational spectroscopy can become an excellent source for decoding electronic structure information of a molecule; in particular providing a new quantitative measure of the intrinsic strength of a chemical bond.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, vibrational spectroscopy has developed into an important analytical tool 1–21 with ample applications in chemistry and beyond 22–31 . Today modern vibrational spectroscopy has much more to offer; detailed information on the electronic structure of a molecule and its chemical bonds is encoded in the normal vibrational modes, ready to be deciphered.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy is an important tool in the field of analytical chemistry and bioanalysis, of which Fourier transform infrared (FTIR) spectroscopy and Raman spectroscopy have been widely used in cancer diagnosis in recent years ( Auner et al, 2018 ; Christensen et al, 2019 ; Baiz et al, 2020 ). In our previous work, we studied the serum samples of patients with lung cancer and healthy people using FTIR spectroscopy and found that the concentrations of protein, lipid, and nucleic acid molecules in the serum of patients with lung cancer were higher than those of healthy people ( Yang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%